Paper 09: Differences in Glenohumeral Range of Motion and Humeral Torsion Between Right-Handed and Left-Handed Major League Baseball Pitchers. Issue 7 (30th July 2022) - Harris, Jeremy; Freeston, Jonathan; Soloff, Lonnie; Himmerick, Daniel; Pipkin, Andrew; Genin, Jason; Schickendantz, Mark; Frangiamore, Salvatore; Maier, Jacob
Objectives: Substantial differences in throwing metrics, like velocity, spin rate and pitcher break, have been observed between left and right-handed pitchers. Elite pitchers have demonstrated significant changes in glenohumeral range of motion and humeral torsion compared to the normal population. Differences in these anatomical parameters between left and right-handed pitchers may explain these performance trends. Furthermore, changes in shoulder range of motion measurements have been associated with different injury risks and challenges in assessing rehabilitation progress. This study seeks to determine if differences in glenohumeral range of motion and humeral torsion exist between left-handed and right-handed pitchers. Methods: 217 MLB pitchers from a single organization were evaluated over a 7-year period from 2013-2020. Range of motion was evaluated by three trained examiners using a Standard Goniometer. Ultrasound scanning was used to determine neutral position of the shoulder and the degree of humeral torsion was measured with a goniometer. The mean and standard deviation were assessed for normality using Shapiro Wilk. Differences between right and left-handed pitchers were assessed using one-way ANOVA. Arm effects were assessed using paired samples t-tests. Results: Right-handed pitchers showed, on average, 13.9 degrees more shoulder external rotation range in their dominant arm compared with their non-dominant arm, whereas left-handers averaged only 2.2 degrees. RHPs showed greater asymmetries in shoulder internal rotation range (13.9 vs 4.8 degrees) and humeral torsion (-23.1 vs -2.2 degrees). Left-handed pitchers showing significantly greater range of non-dominant shoulder flexion (165.8 vs 160.7 degrees) leading to greater flexion deficits in the dominant arm compared to their right-handed counterparts, (7.5 vs 0.0 degrees). Conclusions: Right-handed pitchers demonstrate significantly greater measures of external rotation, humeral retrotorsion, and shoulder flexion compared to left-handed counterparts. The correlation between humeral retrotorsion and increased external rotation indicate that osseus adaptations are a major contributor to range of motion differences associated with handedness. Additionally, these findings may explain observed differences in several throwing metrics between right and left-handed pitchers. Furthermore, knowledge of these differences can inform rehabilitations programs and shoulder maintenance regimens. Table 1. Range of Motion Variables for Right Handed (RHP) and Left Handed (LHP) Professional Baseball Pitchers.* Table 2. Average Velocity in Miles per Hour by Pitch Type and Pitcher Handedness, 2017-2020. a Figure 1. Scatter chart showing the correlation between dominant-arm retrotorsion and external rotation gain in the throwing arm of all pitcher's studied. As retrotorsion increased, the degree of external rotation also increased. Right-handed pitchers were more likely to have higher degrees of both retrotorsion and external rotation gain. Negative values indicate retrotorsion. Figure 2. Box and whisker plot showing the difference in dominant-arm retrotorsion in the dominant throwing arm in left and right-handed pitchers. Dominant-arm| retrotorsion is the difference in torsion between the dominant throwing and non-throwing arm. Right-handed pitchers demonstrated significantly more retrotorsion (negative torsion) in the dominant throwing arm compared to left-handed pitchers.